PASAULIO KNYGOTYROS LEIDINIAI - JAKIMAVIČIŪTĖ, IVETA (Knygotyra, 2010)
Vilniaus universiteto Knygotyros ir dokumentotyros institutas Universiteto g. 3, LT-01513 Vilnius, Lietuva El. paštas: iveta.jakimaviciute@kf.vu.lt